The Influence of Digital Marketing, Management Innovation, and Customer Relationship Management (CRM) on Customer Loyalty with Customer Trust as a Mediating Variable at Sumbertani Agricultural Store in Sempolan - Rozana, Kennis Afriq Febriana (Proceedings Series on Social Sciences & Humanities, 2025)
The increasing use of digital technology in the agricultural sector has transformed customer interaction and loyalty patterns. This study investigates the influence of digital marketing, management innovation, and customer relationship management (CRM) on customer loyalty, with customer trust acting as a mediating variable. Conducted at Sumbertani Agricultural Store in Sempolan, the research applied a quantitative method by distributing structured questionnaires to 100 respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to determine the relationships among variables. The findings indicate that digital marketing and CRM have a significant and direct effect on customer loyalty. In contrast, management innovation does not influence loyalty directly but exerts an indirect effect through customer trust. Additionally, customer trust partially mediates the relationship between the independent variables and loyalty. These results emphasize the role of trust in enhancing customer loyalty and provide insights for agricultural businesses aiming to strengthen their customer base. Implementing digital strategies combined with effective CRM and innovative practices is essential for building long-term loyalty.